DAMPAK PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KARAKTER SISWA - Asmadi; Muhibbin Syah; Ahmad Yasa (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2022)
The number of students who experience moral decline is influenced by the current of modernization, so that professional Islamic Religious Education (PAI) teachers are needed in providing learning so that they are able to suppress the level of decline in student character. The focus of this research is the efforts of PAI teachers in the formation of student character and the impact of teacher professionalism on efforts to build student character. This study aims to describe the efforts of PAI teacher professionalism in shaping students' morals and to describe the significance of PAI teacher professionalism in an effort to build student character in the two schools. The research method used is qualitative research with a phenomenological approach, includes observation, interviews, and documentation. The results of this study are: 1) Professionalism efforts carried out by Islamic Religious Education teachers in shaping the character of students, including: a) Exemplary (qudwah), b) Giving Advice and Motivation, c) Habituation Activities, d) Giving Sanctions and Rewards, e) Building Cooperation between Parents, Schools and the Community, , f) Students' Personal Approach, g) Getting used to applying noble characters, h) Implanting IMTAQ Values ​​and 2) The Impact of Professionalism of Islamic Religious Education Teachers has a significant influence on the formation of students' character, namely by mastering multi competencies that must be possessed, namely Competence Pedagogics, Social Competencies, Personal Competencies and Professional Competencies.